Jejunum Hemolymphangioma Presenting as Chronic Anemia: A Case Report - Liu, Jiao; Zhang, Meng; Li, Yesheng; Chen, Yi; Hong, Yonggang; Huang, Yangqing (Archives of Clinical and Medical Case Reports, 2022)
Background: Hemolymphangioma is a rare disease with congenital malformation of both vascular and lymphatic vessels characterized by cystic dilation. It mostly occurs in cutaneous localizations like head, neck during childhood. Only few cases of hemolymphangioma occur in the small intestine, pancreas, esophagus have been reported. Hemolymphangioma is usually asymptomatic or lack of typical symptoms and the diagnosis is often made as an incidental finding during endoscopy. On rare cases the initial symptoms can be chronic anemia due to gastrointestinal bleeding. They constitute an unusual manifestation and there is a low incidence of this type of tumor. Case Presentation: We report the case of a 42-year-old male, with a 7- month history of chronic anemia requiring blood transfusion. Hemoglobin and Hematocrit count were low, therefore further examinations were required to rule out bleeding sources or other causes of anemia. Double balloon enteroscopy showed a 20×20 mm lesion taking up 30% of the circumference in the proximal jejunum, with raised whitish edges, the center with a vascular appearance, and bleeding spots. Histological sections of the lesion revealed in the lamina propria and submucosal layer of the jejunum several markedly dilated thin-walled lymphatic spaces lined with single layers of flat endothelial cells. The final pathologic diagnosis was submucosal hemolymphangioma. Histological examination confirmed the diagnosis of submucosal hemolymphangioma. Conclusion: The clinical symptoms of hemolymphangioma range from abdominal pain, anemia due to chronic blood loss in gastrointestinal tract, and obstruction to perforation. This case makes the point that hemolymphangioma should be concerned in the differential diagnosis of chronic anemia and other tumors in abdominal cavity with multiple diagnostic m